2000
DOI: 10.1111/j.1601-0825.2000.tb00104.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of mouth cancer: a review of global incidence

Abstract: Mouth cancer (143-145 ICD-9) is a major health problem in many parts of the world. While its incidence is relatively low in most western countries there are some important exceptions to this trend: on the Indian subcontinent and in other parts of Asia it remains one of the most common forms of cancer. This review article summarises the global incidence of mouth cancer using cancer maps. Data have been compiled from the latest edition of Cancer Incidence in Five Continents and recent studies from various locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
1
19

Year Published

2000
2000
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(175 citation statements)
references
References 43 publications
2
153
1
19
Order By: Relevance
“…Comparative worldwide studies have reported its incidence to be much higher in India (Moore et al, 2000;Mishra and Meherotra, 2014). In Chennai, India, oral tongue squamous cell carcinoma (OTSCC) represents 5% and 1.6% of incident cancers of all sites among males and females respectively as per the reports of population based cancer registry of the National Cancer Registry Program.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative worldwide studies have reported its incidence to be much higher in India (Moore et al, 2000;Mishra and Meherotra, 2014). In Chennai, India, oral tongue squamous cell carcinoma (OTSCC) represents 5% and 1.6% of incident cancers of all sites among males and females respectively as per the reports of population based cancer registry of the National Cancer Registry Program.…”
Section: Introductionmentioning
confidence: 99%
“…The trends in epidemiology of oral cancer in Asia in the past decade (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) shows oral tongue as the most frequently affected site (Krishna et al, 2013). Earlier studies report a higher incidence of OTSCC in India compared to other countries (Moore et al, 2000;Elango et al, 2006;Krishnamurthy et al, 2013;Mishra et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because oral cancer is a type of highly malignant tumor with a potent capacity to invade locally and metastasize distantly an approach to decrease tumor's ability to invade and metastasize may facilitate the development of effective adjuvant therapy (10). Oral squamous cell carcinoma is highly resistant to conventional chemotherapy or radiation therapy and the current treatment strategy for carcinomas attempts to attack homogenous cancerous tissues thus the development of novel anticancer drugs is a simple method for remedy of cancer (11). The variability of clinical outcomes in oral cancer patients and the heterogeneity of the disease are the main challenges for the improvement of current treatment modalities (12).…”
Section: Discussionmentioning
confidence: 99%